The contribution of teaching practices and pupils’ initial knowledge to literacy learning - Buisán, Carmen; Rios, Isabel; Tolchinsky, Liliana (Swiss Journal of Educational Research, 2018)
The learning of written language results from a shared contribution of the literacy knowledge pupils bring and the pedagogical instruction they receive. The aims of the present study were (1) to assess children’s emerging literacy knowledge, in terms of both notational and textual aspects, at the beginning of the third year of preschool education; (2) to obtain a detailed picture of teaching practices in initial instruction of written language in nine regions of Spain; and (3) to determine the relationship between these two factors and learning outcomes at the end of the first year of primary education. In spite of having identified three clearly different profiles of teaching practices, results indicate that children’s performance in written language was more strongly associated with their initial literacy level of knowledge than with what the teacher did.A detailed observation of classroom interactions in the context of specific tasks not only enabled us to look more closely at different learning trajectories but also revealed several socio-affective and attitudinal aspects that appear to explain the differences in learning processes.